Patterns of violent specialization: Predictors of recidivism for a cohort of parolees - Schwaner, Shawn L. (American journal of criminal justice, 1998)
Historically, there has been interest in the unfolding of criminal careers, especially in the persistence, specialization, and prediction of violent recidivism. Specialization in violent crime is particularly important as both the public and politicians have called for longer sentences, incapacitation, and prison expansion for violent offenders. However, research on the specialization of violent crime has been largely overlooked in spite of its importance to criminal justice practitioners and public interest. To examine the specialization in crime, this research uses data collected in Ohio in 1989 on a cohort of 3,353 parolees released from prison. Specialization is defined as the exclusive admission to prison for a violent crime with a subsequent violent recidivism offense. Logistic regression is used to delineate predictors of violent specialization. Race, county of commitment, age at release, time served, number of prior felony convictions, and number of prior parole revocations are found to be related to violent specialization.